Antioxidant Activity of Colored Rice Flour with Drying Temperature Variations - Budiman Nur Arifin; Akhmad Mustofa; Yannie Asrie Widanti (Universitas Slamet Riyadi Surakarta, 2023)
Rice is the main product obtained from grain produced by the rice plant (Oryza sativa) whose entire layer has been peeled off and the bran layer has been separated in the form of head rice, whole rice grains, broken rice, and groats. There are several types of pigmented rice such as brown rice, black rice and black glutinous rice. These kinds of rice have not been utilized optimally so that a processing process is needed to increase the economic value of the colored rice. One of the processing is made as flour so that it is durable and easy to distribute and flour can be used as a food processing material that is practical, easy and durable. One of the processed rice is rice flour. Colored rice flour is the result of processing brown rice, black rice and black glutinous rice by milling or flouring. This study aims to determine the optimal temperature in the manufacture of colored rice flour in order to obtain colored rice flour which has high antioxidant activity and high anthocyanins. The result of flouring is in the form of very fine grains. Flour has a low water content so it is more durable and long lasting. In order to reduce the moisture content, drying is carried out. The study used a completely randomized design (RAL) consisting of 2 factors. The first factor was the type of colored rice, while the second factor was the drying temperature of rice flour. The optimal treatment results were a combination of black glutinous rice flour treatment and a drying temperature of 45°C for 60 minutes, the following results were obtained: water content 7.44%, antioxidant activity by DPPH method 69.89%, antioxidant activity by FRAP method 81.35%, yield 25.29%, total phenol 175.85 mg/kg, and anthocyanin levels 327.10 ppm. Changes in temperature during the drying process of colored rice will affect the characteristics of the colored rice.